The five senses : how our bodies work - Dineen, Jacqueline (London : Macmillan Education Ltd, 1989)
Discusses the functions, disorders, and care of the five senses.
Includes index.
Keywords: Senses and sensation -- Juvenile literature; Senses and sensation